Variáveis associadas a congestão pulmonar avaliadas pelo ultrassom pulmonar em pacientes diabéticos submetidos à hemodialise - Lima Neto, José Antônio de (2017)
Aim: We investigated possible independent predictors of lung congestion among diabetics with end-stage renal disease (ESRD) on maintenance hemodialysis (HD), using chest ultrasound to detect extracellular lung water. Methods: We studied 73 patients with diabetes as the primary cause of ESRD, undergoing regular HD. Lung congestion was assessed by counting the number of lung comets detected by chest ultrasound. Volemic status was assessed by bioimpedance analysis and cardiac function by echocardiography. The collapse index of the inferior cava vena (ICV) was calculated by dividing the ICV diameter after forced expiration to the diameter during inspiration, measured by ultrasonography. All patients were classified according to NYHA system. Correlations of the number of lung comets with continuous variables and comparisons regarding the number of lung comets according to categorical variables were performed. Multivariate linear regression was used to test the variables as independent predictors of the number of lung comets. Results: None of the variables related to volemic status (assessed by bioimpedance) and cardiac function (evaluated by echocardiography) were predictors of the number of lung comets. In the multivariate analysis, only the ICV collapse index (b=45.038; p<0.001) and NYHA classes (b=13.995; p=0.006) were independent predictors of the number of lung comets. Conclusion: Clinical evaluation based on NYHA score and measurement of the collapsed ICV index were found to be more reliable than bioimpedance analysis to predict lung congestion among diabetics on HD.